The impact of financial liberalization on private savings: The case of Maghreb countries Arabia - Maher, Zaied (Quantitative Economics and Management Studies, 2025)
The concept of financial liberalization emerged in the early 1970s from the seminal works of McKinnon (1973) and Shaw (1973). These authors conceptualized financial sector liberalization as a key mechanism through which financial development could enhance economic growth. Their theory was well received by international institutions such as the International Monetary Fund (IMF) and the World Bank, which later promoted financial liberalization as a cornerstone policy to stimulate development in emerging economies.According to this framework, liberalizing the financial sector facilitates more efficient mobilization and allocation of financial resources. It also strengthens the coordination between savings and investment, thereby contributing to macroeconomic stability and long-term growth. This article aims to empirically assess the impact of financial liberalization on private savings. To this end, we employ the Ordinary Least Squares (OLS) method along with stationarity tests to examine the relationship between financial liberalization indicators and private savings in Maghreb Arab countries over the 2008-2016 period. The econometric results reveal that economic growth achieved during the period was accompanied by an increase in real per capita income, which in turn positively influenced private savings levels across the region.